Self-assessment of the outcome of early medical abortion versus clinic follow-up in India: a randomised, controlled, non-inferiority trial - Dr. Kirti Iyengar, MD; Mandira Paul, MSc; Sharad D Iyengar, MD; Marie Klingberg-Allvin, PhD; Birgitta Essén, MD; Prof. Johan Bring, PhD; Sunita Soni, MSc; Prof. Kristina Gemzell-Danielsson, MD (Elsevier, 2015)
Background: The need for multiple clinical visits remains a barrier to women accessing safe legal medical abortion services. Alternatives to routine clinic follow-up visits have not been assessed in rural low-resource settings. We compared the effectiveness of standard clinic follow-up versus home assessment of outcome of medical abortion in a low-resource setting. Methods: This randomised, controlled, non-inferiority trial was done in six health centres (three rural, three urban) in Rajasthan, India. Women seeking early medical abortion up to 9 weeks of gestation were randomly assigned (1:1) to either routine clinic follow-up or self-assessment at home. Randomisation was done with a computer-generated randomisation sequence, with a block size of six. The study was not blinded. Women in the home-assessment group were advised to use a pictorial instruction sheet and take a low-sensitivity urine pregnancy test at home, 10-14 days after intake of mifepristone, and were contacted by a home visit or telephone call to record the outcome of the abortion. The primary (non-inferiority) outcome was complete abortion without continuing pregnancy or need for surgical evacuation or additional mifepristone and misoprostol. The non-inferiority margin for the risk difference was 5%. All participants with a reported primary outcome and who followed the clinical protocol were included in the analysis. This study is registered with ClinicalTrials.gov, number NCT01827995. Findings: Between April 23, 2013, and May 15, 2014, 731 women were recruited and assigned to clinic follow-up (n=366) or home assessment (n=365), of whom 700 were analysed for the main outcomes (n=336 and n=364, respectively). Complete abortion without continuing pregnancy, surgical intervention, or additional mifepristone and misoprostol was reported in 313 (93%) of 336 women in the clinic follow-up group and 347 (95%) of 364 women in the home-assessment group (difference −2·2%, 95% CI −5·9 to 1·6). One case of haemorrhage occurred in each group (rate of adverse events 0·3% in each group); no other adverse events were noted. Interpretation: Home assessment of medical abortion outcome with a low-sensitivity urine pregnancy test is non-inferior to clinic follow-up, and could be introduced instead of a clinic follow-up visit in a low-resource setting. Funding: Swedish Research Council and Swedish International Development Agency.